A Study on ATM Services and Customer Satisfaction of Commercial Bank in Itahari, Sunsari Nepal - KC, Pradeep (Journal of Vishwa Adarsha College, 2024)
The analysis of the changing behavior of customers is crucial, and more significant to understanding behavioral finance. The objective of the study was to assess the satisfaction status of customers using ATM services. The study followed an analytical research design using a quantitative research approach. Among the ATM subscribers in Itahari, Sunsari, 140 respondents were chosen conveniently. A structured questionnaire with a five-point Likert scale was designed to collect primary data. Mean and standard deviations were used to assess the status of customer satisfaction with ATM Services, while correlation and linear regression were used to examine their associations. The results revealed that the customers are moderately satisfied with the use of ATM services. In addition, this study suggested that ATM services have a significant effect on customer satisfaction. Among the factors, the transaction fee is found a key factor influencing customer satisfaction, followed by customer support and transaction speed. This study supports the bank managers to top-up customers’ satisfaction by implementing the findings.